Portfolio Optimization by Means of Multiple Tandem Certainty-Uncertainty Searches - Chow, Brian G. (RAND Corporation, 2023)
This paper describes a new approach to optimization under uncertainty that is aimed at finding the optimal solution to a problem by designing a number of search algorithms or schemes in a way that allows analysts to apply to a problem that contains a significantly larger number of decision variables, uncertain parameters, and uncertain scenarios than they have had to contend with until now.